Reconocemos nuestras características y cualidades - Rodriguez Mena, Dinmert (2018)
In this learning session, the children of the second grade will learn to recognize, accept and value their physical characteristics (height, color, hair, skin color, weight, eye color, etc.) and the different qualities and Once you know them, we must give you the opportunity to demonstrate them frequently. As a consequence of this, the child must learn to reinforce himself, that is, to direct positive thoughts and comments about himself. This will allow you to feel happier, at ease with yourself and increase your self-esteem and have greater security in the school groups with which you interrelate as well as in your family and social environment. For this, a series of activities has been planned, which will lead them to value themselves as unique and valuable people, accepting themselves as they are.